Organizational Development Republic of Indonesia Civil Servant Corps (KORPRI) at the National Counterterrorism Agency (BNPT) - Rizki Montheza; Fernandes Simangunsong; Mansyur Ahmad (Sean Institute, 2024)
This research aims to examine and analyze the Organizational Development of the Indonesian Civil Servant Corps (KORPRI) at the National Counterterrorism Agency (BNPT). The research focus includes analysis of supporting and inhibiting factors in organizational development, as well as strategies for overcoming these obstacles. The theoretical framework used is the 4R perspective (Reframing, Restructuring, Revitalize, Renewal) proposed by Gouillart and Kelly in Simangunsong (2014). This research uses a qualitative approach with data collection techniques through interviews, observation and documentation studies. Data analysis was carried out using the Miles and Huberman approach, which includes data reduction, data presentation, and drawing conclusions. Informants in this research included various officials and members of KORPRI BNPT, including the Chair of KORPRI BNPT, Deputy Chair 1 of KORPRI BNPT, Head of the BNPT Personnel Section, as well as members from various fields within KORPRI BNPT. The research results show that the development of KORPRI at BNPT has not been optimal due to obstacles such as low funding allocation, readiness of human resources, participation in supporting organizational activities, and experience in sustainable and integrated KORPRI management.